PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, KOMPENSASI DAN IKLIM KERJA TERHADAP PROFESIONALISME GURU DI SD NEGERI SE-KECAMATAN SLAWI KABUPATEN TEGAL - Indah Eko Cahyani; Sunandar Sunandar; Yovitha Yuliejantiningsih (Magister Manajemen Pendidikan, Universitas PGRI Semarang, 2017)
The objectives of this study are: (1) to analyze the influence of the principal's leadership on teacher professionalism, (2) to analyze the influence of the principal's influence on the professionalism of the teacher, (3) to analyze the influence of the work climate on professionalism, compensation and work climate together towards the professionalism of teachers.The study was conducted in thirty-seven elementary schools in Slawi sub-district with a population of 439 people and a sample of 82 people. Samples were taken randomly proportionately. Data collection in this study used the questionnaire as an instrument. Test of validity and reliability, test of normality and linearity, test of simple linear regression and multiple regression used facility program SPSS for Windows 21.0.The result of the research shows that: (1) there is influence of principal leadership toward teacher professionalism is 67,9% (2) there is influence of compensation to teacher professionalism equal to 61,8% (3) the working climate on professionalism of teachers is 71.8% (4) there is influence of principal leadership, compensation, and work climate together toward professionalism of teachers in SD Negeri in Slawi District of Tegal Regency is 69,3%.Suggested suggestions for improving teacher professionalism through continuous learning. In addition, for certified teachers to always improve their professionalism by following up to higher education, training, training, workshops, seminars or active in MGMP activities.